2021
DOI: 10.3389/fmed.2021.806899
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Remodeling in Pulmonary Arterial Hypertension: The Potential Involvement of Innate and Adaptive Immunity

Abstract: Pulmonary arterial hypertension (PAH) is a severe disease with high morbidity and mortality. Current therapies are mainly focused on vasodilative agents to improve prognosis. However, recent literature has shown the important interaction between immune cells and stromal vascular cells in the pathogenic modifications of the pulmonary vasculature. The immunological pathogenesis of PAH is known as a complex interplay between immune cells and vascular stromal cells, via direct contacts and/or their production of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The mechanism of action remains largely unclear. Persistent injury to endothelial cells, activation of innate and adaptive immunity and downstream effects on smooth muscle cells and fibroblasts results in extracellular matrix production and vascular remodeling [ 18 ]. Different auto-antibodies like anti-endothelial cell antibodies (AECAs) may play an important role in fibroblast activation [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action remains largely unclear. Persistent injury to endothelial cells, activation of innate and adaptive immunity and downstream effects on smooth muscle cells and fibroblasts results in extracellular matrix production and vascular remodeling [ 18 ]. Different auto-antibodies like anti-endothelial cell antibodies (AECAs) may play an important role in fibroblast activation [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the aortic banding model of Ws/Ws mast cell-deficient rats with a small deletion in the tyrosine kinase domain of the c-kit gene, PH, and pulmonary vascular remodeling in left-sided heart failure were attenuated compared to control rats, suggesting that the presence of mast cells may exacerbate the pathology of PH [ 20 ]. Further, several studies have shown that granule contents released by mast cells are deeply involved in development of PH [ 21 , 22 , 23 ]. Mast cell stabilizers that inhibit degranulation, such as cromolyn and disodium cromoglycate (DSCG), improve pulmonary vascular remodeling in various PH rat models [ 13 , 24 , 25 ].…”
Section: Role Of Mast Cells In Pulmonary Vascular Remodelingmentioning
confidence: 99%
“…The blockage in the pulmonary vessels may progress to right-side heart failure which is the primary cause of high morbidity and mortality associated with PAH (Refs 124 , 125 , 126 ). At the cellular level, the main changes in PAH include proliferation of fibroblasts, infiltration of immune cells and proliferation of PASMCs (Refs 125 , 127 , 128 , 129 , 130 ). The above factors mediate the development of a vascular remodelling phenotype, called ‘neointimal lesions’, resulting in the elevation of pulmonary vascular resistance and ultimately heart failure (Refs 64 , 131 , 132 , 133 ).…”
Section: Notch3 Signalling and Acute Or Chronic Lung Diseasementioning
confidence: 99%